Determination of the Optimal Buoy Shape for A Concept Wave Energy Converter to Harness Low Amplitude Sea Waves using Numerical Simulation - Olakunle Kayode; Olufemi Adebola Koya; Titus Oluwasiji Ajewole (Institut Teknologi Sepuluh Nopember, 2019)
This research investigates the optimal buoy shape for a conceptual point absorber Wave Energy Converter (WEC) for harnessing low amplitude sea waves characteristic of the Gulf of Guinea coast. It has been established that shape of buoy is one of the main parameter affecting the efficiency of a point absorber WEC. Based on best buoy shapes as reported in literature, two shapes are selected for comparison: cone-cylinder composite buoy and Concave wedge shaped buoy. The WEC’s buoy and the power take off were mathematically modelled as a mass-spring-damper system. The buoys hydrodynamic coefficients were computed using strip theory, while the simulation in the time domain was executed using MATLAB. Impute parameters referred to as the sea states, in five levels, were described by the significant wave height Hs and the corresponding energy period Te, typical of the gulf. Output parameters are displacement, velocity, acceleration and force of the buoys, as well as the instantaneous power output of the WEC. For the levels considered, the optimum sea state for the two buoys peaked at level 4 (Hs = 1.5 m, Te = 14 s), with concave wedge buoy having an optimal power output of 8 kW while that of cone-cylinder being 3.7 kW. For the other levels the wedge buoy also consistently gives relatively greater power output than the cone cylinder buoy.